2021
DOI: 10.1002/2211-5463.13250
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of HPRT1 is associated with poor prognosis in head and neck squamous cell carcinoma

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
(68 reference statements)
2
19
0
Order By: Relevance
“…It has been reported that HPRT1 is significantly elevated in multiple cancer types ( 53 , 54 ) and is associated with a poor prognosis due to the increased demand for nucleotide synthesis during tumor cell proliferation ( 55 , 56 ). In both HNSCC and its subclass oral squamous cell carcinoma, multiple studies have demonstrated that HPRT1 was overexpressed and significantly correlated with the poor prognosis of patients ( 57 , 58 ). HPRT1 was also found to be associated with drug resistance, such as cisplatin, in cancer cells and has been proposed as a therapeutic target of chemotherapeutic drugs ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that HPRT1 is significantly elevated in multiple cancer types ( 53 , 54 ) and is associated with a poor prognosis due to the increased demand for nucleotide synthesis during tumor cell proliferation ( 55 , 56 ). In both HNSCC and its subclass oral squamous cell carcinoma, multiple studies have demonstrated that HPRT1 was overexpressed and significantly correlated with the poor prognosis of patients ( 57 , 58 ). HPRT1 was also found to be associated with drug resistance, such as cisplatin, in cancer cells and has been proposed as a therapeutic target of chemotherapeutic drugs ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…It plays a crucial role in regulating the cell cycle and has been reported to be overexpressed in a variety of cancers ( 45 ). The elevated expression of the HPRT1 gene is associated with the progression of HNSCC, which may serve as a useful indicator for early detection, risk stratification, and targeted therapy in HNSCC patients ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…HPRT1 is an important protein that provides the necessary components for cell growth and is highly expressed in most tissues. HPRT1 has traditionally been used as a housekeeping gene; however, many recent studies have found a potential relationship with various types of cancer [ 6 , 7 , 8 ]. HPRT1 overexpression was significantly correlated with the poor prognosis of patients with HNSCC [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…HPRT1 has traditionally been used as a housekeeping gene; however, many recent studies have found a potential relationship with various types of cancer [ 6 , 7 , 8 ]. HPRT1 overexpression was significantly correlated with the poor prognosis of patients with HNSCC [ 7 ]. HPRT1 was also found to be associated with drug resistance in cancer cells and has been proposed as a therapeutic target of chemotherapeutic drugs [ 9 ].…”
Section: Introductionmentioning
confidence: 99%